Exploring Preservice Teachers' Career Choices: A Q‐Methodological Study - Polat, Murat (Psychology in the schools, 2025)
ABSTRACT This study explores the perspectives of preservice teachers on their career choice, focusing on the interplay between intrinsic, extrinsic, and interpersonal factors. Conducted with 48 preservice teachers from a state university in Eastern Türkiye, the study employed 58 Q‐statements for data collection. Findings reveal that while financial stability remains a significant factor, career motivations extend beyond economic concerns. Participants' motivations were grouped into six interconnected themes: service, influence on others, time compatibility, interpersonal relationships, material benefits, and continuity. While some emphasized job security and financial predictability, others highlighted teaching's social contribution and personal fulfillment. The study offers valuable insights into how financial motivations intersect with deeper vocational values, shedding light on the complex nature of career decision‐making in teacher education. These findings have significant implications for both teacher education policy and career guidance practices. In particular, integrating structured guidance services into teacher education programs can better support preservice teachers in aligning their diverse aspirations with the realities of the profession. Such efforts may enhance teacher recruitment, satisfaction, and retention. Future research should explore how these motivations evolve over time, especially in relation to shifting economic conditions and educational policy reforms. Summary Preservice teachers prioritize financial stability, job security, and interpersonal factors in career decisions. Q methodology reveals a complex interplay between intrinsic, extrinsic, and altruistic motivations. Findings inform teacher training, recruitment, and policy strategies to enhance retention and satisfaction.